THE ROLE OF PSYCHOLOGY IN THE ACADEMIC ACHIEVEMENT OF FOREIGN LANGUAGE LEARNING (Journal of Universal Science Research, 2024)
The role of psychology in the academic achievement of foreign language learning is multidimensional, encompassing cognitive, emotional, and social factors that shape the language acquisition process. Psychological principles provide insights into how learners process, retain, and apply new linguistic knowledge, highlighting the importance of motivation, memory, and anxiety management. Motivation, a key psychological factor, drives learners' engagement and persistence. Intrinsic motivation, such as personal interest or cultural appreciation, often leads to better outcomes, while extrinsic motivators, such as career prospects, can sustain effort in challenging tasks.Cognitive processes like working memory and long-term memory underpin vocabulary acquisition and grammatical understanding. Strategies like spaced repetition and active recall, derived from psychological research, enhance retention. Emotional factors, including anxiety and self-efficacy, also play a critical role. Foreign language anxiety can impede performance, but interventions such as mindfulness and positive reinforcement foster confidence and reduce fear of failure. Self-efficacy—the belief in one’s ability to succeed—encourages learners to persevere through difficulties.